1999
DOI: 10.1007/s002679900191
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Riparian Cottonwoods to Alluvial Water Table Declines

Abstract: / Human demands for surface and shallow alluvial groundwater have contributed to the loss, fragmentation, and simplification of riparian ecosystems. Populus species typically dominate riparian ecosystems throughout arid and semiarid regions of North American and efforts to minimize loss of riparian Populus requires an integrated understanding of the role of surface and groundwater dynamics in the establishment of new, and maintenance of existing, stands. In a controlled, whole-stand field experiment, we quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
236
0
5

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 252 publications
(252 citation statements)
references
References 33 publications
11
236
0
5
Order By: Relevance
“…The focus of irrigation to the riparian corridors has placed intense competition between water resources for people versus the environmental flows that are required to maintain shallow aquifers and associated GDEs. Of further risk to riparian GDEs and agriculture, groundwater extraction and land use change threaten riparian ecosystems (Scott et al, 1999;Nippert et al, 2010;Pert et al, 2010). Thus, many studies have been undertaken over several decades to investigate the water use of GDEs in south-western North America (van Hylckama, 1970;Gay and Fritschen, 1979;Sala et al, 1996;Devitt et al, 1998;Goodrich et al, 2000a;Cleverly et al, 2002;Scott et al, 2004;Nagler et al, 2005b).…”
Section: The Gnangara Moundmentioning
confidence: 99%
See 1 more Smart Citation
“…The focus of irrigation to the riparian corridors has placed intense competition between water resources for people versus the environmental flows that are required to maintain shallow aquifers and associated GDEs. Of further risk to riparian GDEs and agriculture, groundwater extraction and land use change threaten riparian ecosystems (Scott et al, 1999;Nippert et al, 2010;Pert et al, 2010). Thus, many studies have been undertaken over several decades to investigate the water use of GDEs in south-western North America (van Hylckama, 1970;Gay and Fritschen, 1979;Sala et al, 1996;Devitt et al, 1998;Goodrich et al, 2000a;Cleverly et al, 2002;Scott et al, 2004;Nagler et al, 2005b).…”
Section: The Gnangara Moundmentioning
confidence: 99%
“…can be very sensitive to groundwater decline, resulting in reductions of ET, productivity and canopy conductance as a consequence of increases in vapour pressure deficit that are correlated with depth-to-groundwater (Gazal et al, 2006;Kochendorfer et al, 2011). Branch sacrifice, partial crown dieback and mortality commonly occur in Populus following substantial groundwater drawdown (Mahoney and Rood, 1991;Kranjcec et al, 1998;Scott et al, 1999;Rood et al, 2000Rood et al, , 2003Cooper et al, 2003). However, stomatal closure and crown dieback in Populus can prevent total hydraulic failure, and thereby minimise mortality rates, by maintaining favourable xylem water potentials within the remainder of the crown (Amlin and Rood, 2003).…”
Section: The Gnangara Moundmentioning
confidence: 99%
“…Use of groundwater by phreatophytes is highest during the driest season of the year when alternative water sources become depleted and transpirational demand is highest. It is also suggested that phreatophytes are susceptible to the rate as well as season of drawdown (Mahoney and Rood 1992;Stromberg and Patten 1992;Tyree et al 1994;Scott et al 1999Scott et al , 2000Groom et al 2000;Shatfroth et al 2000;Horton et al 2001;Eamus et al 2006a) by having a higher rate of water-table decline than fine-root elongation rate, and/or lowering the water table during a time other than the root growth season (Sorenson et al 1991). Low magnitude and rates of change in groundwater levels as opposed to rapid drawdown, may allow intra-and inter-generational adaptation and persistence of phreatophytes (Scott et al 1999;Shatfroth et al 2000).…”
Section: Groundwater-dependent Ecosystem Management: Current Issuesmentioning
confidence: 99%
“…However, there is little information currently available on the process of adaptation to altered groundwater availability. Some research has suggested that populations of phreatophytes may be able to adapt to low rates/magnitudes of groundwater drawdown through a combination of modification of fine-root distribution and corresponding altered water-source partitioning (Scott et al 1999;Shatfroth et al 2000). However, the magnitude, rate and seasonality of water-table reductions that permit (if at all) adaptation are not quantified, despite previous attempts to classify Banksia response by using predominately empirical relationships (Froend and Loomes 2004).…”
Section: Groundwater-dependent Ecosystem Management: Current Issuesmentioning
confidence: 99%
“…Physiological responses result in reduced stomatal conductance, transpiration, leaf internal CO 2 concentration, carbon isotope discrimination (an index of water use efficiency and time integrated carbon assimilation) and xylem pressure potentials (Pockman and Sperry, 2000;Merritt et al, 2009). Other plant attributes express long-term responses to reduced water availability, including leaf abscission and leaf death (Merritt et al, 2009), increased leaf thickness and reduced leaf size (Rood et al, 2003), reduced shoot and stem growth (Stromberg and Patten, 1996;Scott et al, 1999;Rood et al, 2003), decreased vessel diameters (February and Manders, 1999;Schume et al, 2004) and increased wood density (Jacobsen et al, 2007). Severe water stress may lead to xylem cavitation, branch dieback and ultimately death (Tyree et al, 1994;Scott et al, 1999;Merritt et al, 2009).…”
mentioning
confidence: 99%